Profesionalime Guru Sekolah Dasar - Astuti, Indri (Jurnal Visi Ilmu Pendidikan, 2009)
Recently the demand on teachers profesionalism is one of the most important agenda in our National Education System. Based on the regulation mode by government about the National Standard of Education, it forces every parties involved in educational system to accelerate the improvement the quality of learning and education the aims are done through preparing and improving the teachers skill professionally and also by managing the educational supporting elements. In improving the Elementary School teacher professionalism, the Departement of Education has done this by preparing Elementary School teacher competency based as the guideline. It is also used for measuring the competency level the teacher has. Morever it can be used as guidance and improvement of the teachers profesionalism. Kata-kata Kunci: Profesionalisme Guru , Standar Kompetensi, Sekolah Dasar